A Dual-Color Bioluminescence Reporter Mouse for Simultaneous in vivo Imaging of T Cell Localization and Function - Kleinovink, Jan Willem; Mezzanotte, Laura; Zambito, Giorgia; Fransen, Marieke F.; Cruz, Luis J.; Verbeek, J. Sjef; Chan, Alan; Ossendorp, Ferry; Löwik, Clemens (Frontiers in Immunology, 2019)
Non-invasive imaging technologies to visualize the location and functionality of T cells are of great value in immunology. Here, we describe the design and generation of a transgenic mouse in which all T cells constitutively express green-emitting click-beetle luciferase (CBG99) while expression of the red-emitting firefly luciferase (PpyRE9) is induced by Nuclear Factor of Activated T cells (NFAT) such as during T cell activation, which allows multicolor bioluminescence imaging of T cell location and function. This dual-luciferase mouse, which we named TbiLuc, showed high constitutive luciferase expression in lymphoid organs such as lymph nodes and the spleen. Ex vivo purified CD8+ and CD4+ T cells both constitutively expressed luciferase, whereas B cells showed no detectable signal. We cross-bred TbiLuc mice to T cell receptor-transgenic OT-I mice to obtain luciferase-expressing naïve CD8+ T cells with defined antigen-specificity. TbiLuc*OT-I T cells showed a fully antigen-specific induction of the T cell activation-dependent luciferase. In vaccinated mice, we visualized T cell localization and activation in vaccine-draining lymph nodes with high sensitivity using two distinct luciferase substrates, D-luciferin and CycLuc1, of which the latter specifically reacts with the PpyRE9 enzyme. This dual-luciferase T cell reporter mouse can be applied in many experimental models studying the location and functional state of T cells.